Le bornage de l’alpage de la Grassaz à Peisey (Tarentaise, xv e siècle) - Constance Toppin (Frontière·s)
On July 3, 1412, representatives from the communities of Landry and Peisey, in the Tarentaise Valley, claim in front of arbitrators and mediators responsible to bring peace and resolve conflicts that the source of the tensions between the two parishes is the property lines deemed obscuri, dark. The border and all the elements delimiting the shared mountain pasture of la Grassaz, used by the members of both communities must be redrawn.Landry and Peisey are both faced, like many medieval and modern communities, with the difficulties inherent to the exploitation of communal resources and spaces, especially alpine pastures. Those high-altitude pastures (pascua) shaped by humans across the millennia for the rearing of livestock, complete the food-producing polyculture of these mountain farmers.Using the example of two rural communities, this paper highlights techniques of physical demarcation, with the tracing of a border between a communal space, la Grassaz, collectively exploited by Landry and Peisey, and the territory specific to Peisey